Aspect, validity, and reliability family support perception scale for substance abuse disorders - Supriyanto, Agus; Hendiani, Nurlita (Universitas PGRI Madiun, 2018)
People perception of Substance Abuse Disorders (GPZ) who are undergoing rehabilitation program on family support has a strong role recovery and relapse prevention. Measuring perception of family support is useful for family counseling development. The goal of research to find aspects of perception and a form family support from people with GPZ to recover from drug addiction on family support perception scale instruments. The research uses mixed methods approach with sequential transformative. Research instrument form documentation study in the form of text analysis, interview, and survey on individual GPZ/ N = 217. The research analysis with qualitative descriptive analysis of journal and book study, focus group discussion to the determination of statement points, and quantitative descriptive analysis from different test result to know validity and reliability of the instrument. The findings reveal the concept and operationalization of family support perception through two perception aspects, ie cognition, and affection. Forms of family support include (1) emotional support, (2) award support, (3) information support, and (4) concrete support. The family support perception scale has 46 valid statements with the value coefficient of Corrected Item-Total Correlation â‰¥ 0.148. The reliability coefficient of the family supported perception scale is 0.861 with the high-reliability category. The family support perception scale can be used to identify the level of family support on people with GPZ from drug addiction.